Determining the helical tilt of membrane peptides using electron paramagnetic resonance spectroscopy - Newstadt, Justin P. (2008)
Theoretical calculations of hyperfine splitting values derived from the EPR spectra of TOAC spin labeled rigid aligned α-helical membrane peptides reveal a unique periodic variation. In the absence of helical motion, a plot of the corresponding hyperfine splitting values as a function of residue number results in a sinusoidal curve that depends on the helical tilt angle that the peptide makes with respect to the magnetic field. Motion about the long helical axis reduces the amplitude of the curve and averages out the corresponding hyperfine splitting values. The corresponding spectra can be used to determine the director axis tilt angle from the TOAC spin label, which can be used to calculate the helical tilt angle due to the rigidity of the TOAC spin label. Additionally, this paper describes a method to experimentally determine this helical tilt angle from the hyperfine splitting values of three consecutive residues.